Excitation dependent multicolor emission and photoconductivity of Mn, Cu doped In2S3 monodisperse quantum dots. (2nd March 2016) - Ghosh, Sirshendu; Saha, Manas; Ashok, Vishal Dev; Chatterjee, Arijit; De, S K
Abstract: Indium sulphide (In2 S3 ) quantum dots (QDs) of average size 6 ± 2 nm and hexagonal nanoplatelets of average size 37 ± 4 nm have been synthesized from indium myristate and indium diethyl dithiocarbamate precursors respectively. The absorbance and emission band was tuned with variation of nanocrytal size from very small in the strong confinement regime to very large in the weak confinement regime. The blue emission and its shifting with size has been explained with the donor–acceptor recombination process. The 3d element doping (Mn 2+ and Cu 2+ ) is found to be effective for formation of new emission bands at higher wavelengths. The characteristic peaks of Mn 2+ and Cu 2+ and the modification of In 3+ peaks in the x-ray photoelectric spectrum (XPS) confirm the incorporation of Mn 2+ and Cu 2+ into the In2 S3 matrix. The simulation of the electron paramagnetic resonance signal indicates the coexistence of isotropic and axial symmetry for In and S vacancies. Moreover, the majority of Mn 2+ ions and sulphur vacancies (VS ) reside on the surface of nanocrystals. The quantum confinement effect leads to an enhancement of band gap up to 3.65 eV in QDs. The formation of Mn 3d levels between conduction band edge and shallow donor states is evidenced from a systematic variation of emission spectra with the excitation wavelength. In2 S3 QDs have been established as efficient sensitizers to Mn and Cu emission centers. Fast and slow components of photoluminescence (PL) decay dynamics in Mn and Cu doped QDs are interpreted in terms of surface and bulk recombination processes. Fast and stable photodetctors with high photocurrent gain are fabricated with Mn and Cu doped QDs and are found to be faster than pure In2 S3 . The fastest response time in Cu doped QDs is an indication of the most suitable system for photodetector devices.